HUBUNGAN KONSEP DIRI DENGAN PERILAKU SEKSUAL BERESIKO PADA REMAJA - Wina Winingsih; Tetti Solehati; Taty Hernawaty (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Breast cancer is the most common invasive cancer in women throughout the world and the second highest cause of cancer death after lung cancer. The purpose of this study was to review a variety of nursing management in breast cancer patients. Research methods: searching strategy was carried out in four data bases namely PUBMED, EBSCO, COCHRANE, and PROQUEST. All databases were chosen with the consideration that all databases were credible in the health and medical fields. The article criteria were a study published in English, published in 2015-2019, and used a Randomized Control Trial study. Researchers found 22 studies that it included the research criteria, namely interventions for nursing management in breast cancer patients. Results: Nursing management for breast cancer patients consisted of interventions, programs and screening. Interventions that can be applied to breast cancer patients consisted of interventions that can reduce anxiety, pain, fatigue, menoupouse symptoms, improve quality of life, physical examination results, physical activity, and cope with nausea. Programs for breast cancer patients consisted of: programs for fulfilling nutrition, physical activity to reduce mucositis and lymphoma, PIE (to increase knowledge, treatment techniques, and increase discomfort). Screening to find out the problems of patients with breast cancer. Conclusion: all interventions, programs, and screening are effective in nursing management for breast cancer patients.